Pre-sowing treatments in mango: Regression analysis between germination parameters and vigour - Reshma, U. R.; Simi, S. (Journal of Tropical Agriculture, 2019)
A study was undertaken during the year 2017-18 at the Department of Pomology and Floriculture, College of Agriculture, Vellayani, Thiruvananthapuram to assess the germination behaviour of mango stones as influenced by various pre-sowing treatments. The mango stones were soaked for 24 hours in aqueous solutions of GA3 (100 and 200 ppm), KNO3 (1 and 2 ppm), cow dung slurry, water and control. The vigour index-I and vigour index-II had linear negative relationship with number of days taken for initiation of germination and number of days taken for 50 per cent germination. The germination percentage and rate of germination had very high degree of association with vigour index-I (R2 = 0.95 & 0.89) and vigour index-II (R2 = 0.89 & 0.95) respectively. The seedling length and dry weight had almost similar degree of association with vigour index-I (R2 = 0.87& 0.76) and vigour index-II (R2 = 0.93 % 0.85) respectively. The pre-sowing treatments had direct significant influence on germination and growth of mango seedlings, which in turn led to maximum vigour.